Subserous lymphangioma of the sigmoid colon: an uncommon cause of acute abdomen in pediatric patients - Bianca Furlan Fernandes; Érika Neves de Souza Moraes; Francini Rossetto de Oliveira; Gabriel Núncio Benevides; Aloísio Felipe-Silva; Cristiane Rúbia Ferreira; Paulo Sérgio Martins de Alcântara; Flavio Tokeshi; João Augusto dos Santos Martinês; Ângela Espósito Ferronato (University of São Paulo, 2015)
Lymphangioma is a rare, benign lesion derived from a malformation of the lymphatic system, which is more frequently found in the head, neck, and axilla. However, it may be present anywhere in the body, and the diagnosis involves adults as children with some distinct clinical features among them. In pediatric patients, abdominal cystic lymphangioma occurs mostly in the mesentery presenting abdominal pain, intestinal obstruction, or, more rarely, hemorrhage. The authors report the case of a child with a short-course history of fever, abdominal pain, and constipation. The physical examination disclosed the presence of an abdominal mass and signs of peritoneal irritation. Imaging was consistent with a cystic lesion compressing the sigmoid colon and laterally displacing the remaining loops. Exploratory laparotomy was undertaken, and a sigmoidectomy, followed by Hartman's colostomy, was performed. Histological examination revealed the nature of the lesion as a cystic lymphangioma. The authors highlight the clinical features of this entity and call attention to this disease in the differential diagnosis of acute abdomen or abdominal pain, mainly in pediatric patients